Simulation and Modelling of Safety of Roadways in Reverse Horizontal Curves (RHCs): With Focus on Lateral Acceleration - Maziyar Khanjari; Ali Abdi Kordani; Mohammad Zarei (Advances in Civil Engineering)
As a type of horizontal curve, the reverse horizontal curves (RHCs) are one of the most critical types of road locations where many accidents occur due to slippage resulting from the centrifugal force of the vehicles. These crashes can increase dramatically if the RHC is combined with a longitudinal slope (downgrade or upgrade). In this study, by using the vehicle dynamic modeling (VDM) method, the lateral acceleration of vehicles (including E-Class Sedan, E-Class SUV, and Truck) passing through the RHC combined with three scenarios of downgrades, upgrades, and no slope was evaluated. Finally, in order to present the final model, the RHC lateral acceleration model was presented based on the effective parameters, including different design velocities (V), the direct distance between two horizontal curves (D), and different longitudinal slopes (G) by the multiple regression model method. The results of the VDM modeling showed that the slide potential of Sedans, SUVs, and Trucks when crossing the RHC combined with the downgrade was more significant than the upgrade and the no-slope paths. On the other hand, the modeling results showed that the proposed models for Sedans and SUVs with a very high level of importance (R2 = 0.920 and R2 = 0.967) could be used to assess the safety of vehicles crossing the RHC. According to the mentioned models, increasing the speed (V) and reducing the direct distance (D) in both models reduced the lateral acceleration (increased safety) of both Sedans and SUVs.